2003
DOI: 10.1002/jmv.10398
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of human group a rotavirus VP7 and VP4 types circulating in Seoul, Korea between 1998 and 2000

Abstract: Three hundred forty-eight fecal specimens collected from young children with acute diarrhea in Seoul, Korea between January 1998 and February 2000 were examined for G and P types. Of these, 205 samples (59%) were confirmed as group A rotavirus by ELISA for the detection of VP6 antigen. Confirmed rotavirus isolates were characterized using G serotyping ELISA and RT-PCR methodologies for G and P genotyping of the outer capsid proteins VP7 and VP4, respectively. Serotyping of the outer capsid protein, VP7, reveal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
20
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 38 publications
4
20
1
Order By: Relevance
“…However, a high incidence of type P [6] strains, as seen in this study, was also reported among infants with diarrhea in Nigeria, India, and Brazil (1,12,16). An incidence of type P [6] comparable to that found in this study was also reported in the study previously conducted in South Korea (15). In this study, types P [9] and P [10] were found for the first time in Korea.…”
supporting
confidence: 90%
See 1 more Smart Citation
“…However, a high incidence of type P [6] strains, as seen in this study, was also reported among infants with diarrhea in Nigeria, India, and Brazil (1,12,16). An incidence of type P [6] comparable to that found in this study was also reported in the study previously conducted in South Korea (15). In this study, types P [9] and P [10] were found for the first time in Korea.…”
supporting
confidence: 90%
“…We also noticed the emergence of type G4 in the present study. Another study previously conducted in Korea showed an even higher incidence of type G4 (40.9%), although the study was performed with samples from only one city (15). The G types of minor incidence in our study included three strains of type G3 (0.9%) and one strain of type G9 but no strain of type G8, unlike the recent emergence of type G9 in several other countries (2,7,13).…”
contrasting
confidence: 65%
“…Studies in many countries indicate that serotype G1 was the most prevalent and that serotypes G2-G4, and G9 were evenly distributed (Jain et al, 2001;Hoshino et al, 2005). In Korea, G1 was the major genotype until 1997 (Kim et al, 1990;Kim, 1992Kim, , 1993, but this shifted to G4 from 1998 to 2000 (Seo and Sim, 2000;Song et al, 2003). In this study, serotype G2 (51.3%) was predominant and serotypes G1, G4 and G3 followed at 28.6%, 8.7%, and 0.9%, respectively, similar to other reports for the same period (Kim et al, 2002;So et al, 2004).…”
Section: Discussionmentioning
confidence: 95%
“…Until 1997, G1 was the most prevalent strain, regardless of geographic area or season [Kim et al, 1990[Kim et al, , 1999Kim, 1993;Seo and Sim, 2000]. Since 1997, the predominant G type strain shifted to G4 Song et al, 2003;Kang et al, 2005], to G2 Moon et al, 2007], and then to G9 . More recently, our data from a 2-year investigation indicated that the G1 strain has become the most common [Le et al, 2008].…”
Section: Introductionmentioning
confidence: 97%